The influences of corporate culture toward employees’ job performance in Wholesale Banking Department in Scope International (M) Sdn. Bhd / Norita Bachok - Bachok, Norita (Faculty of Business and Management, 2010)
This study is conducted at Scope International (M) Sdn. Bhd. and this research is entitled as “The Influence of Corporate Culture on Employees’ Job Performance in Wholesale Banking Department in Scope International (M) Sdn. Bhd.” The main objective of this project paper is identifying the main factor that contributes to corporate culture issues towards employees’ performance in this organization. The researcher has adopted the descriptive research on the issue. Then the researcher’s sampling design is the probability sampling which is stratified sampling method and 60 questionnaires were distributed to employees at this organization. The theoretical framework of this study consists of dependent variable and independent variables. The dependent variable is employees’ job performance while the independent variables are teamwork, organization communication, reward and recognition, also training and development. Data collected and evidences are being processed by using Statistical Package for Social Science (SPSS) program. The analysis includes the reliability, frequency distribution, descriptive analysis, and correlation. Based on the findings, there were hypothesized that are positive relationship exist between these variables. Result of the correlation indicates that the highest reward and recognition scores are associated with the employees’ performance. These correlations also strengthen the ranking of the independent variables. Reward and recognition is the main factor of employees’ job performance. The output also confirms the result that a significant positive relationship exists between other independent.